Wave solutions of the DMBBM equation and the cKG equation using the simple equation method - Sanjun, Jiraporn; Chankaew, Aungkanaporn (Frontiers in Applied Mathematics and Statistics, 2022)
In this article, we transform the (1+1)-dimensional nonlinear dispersive modified Benjamin-Bona-Mahony (DMBBM) equation and the (2+1)-dimensional cubic Klein Gordon (cKG) equation, which are the nonlinear partial differential equations, into the nonlinear ordinary differential equations by using the traveling wave transformation and solve these solutions with the simple equation method (SEM) with the Bernoulli equation. Two classes of exact explicit solutions-hyperbolic and trigonometric solutions of the associated NLEEs are characterized with some free parameters, we obtain the kink waves and periodic waves.